Introduction to Ecectrodynamics - Griffiths, David J. (India : Prentice Hall., 1999)
Engineering
Keywords: Electrodynamics; Electronics; Dynamics; Vector Analysis; Electrostatics; Electric Field; MagnetostaticsMagnetic Fields; Electromagnetic Waves; Radiation; Electrodynamics Relativity